Níveis de adubação N-K do abacaxizeiro 'BRS Imperial' no extremo Sul da Bahia - Oliveira, Arlene Maria Gomes [UNESP] (2014)
Fertilization has great effect on the production and quality of pineapple fruits. This study aimed to evaluate the effect of N and K2O levels in vegetative development, production and post-harvest fruit quality of pineapple ‘BRS Imperial '. Four levels of N (0, 160, 320 and 550 kg ha-1) and four levels of K2O (0, 240, 480 and 600 kg ha-1), in a randomized block design with five replicates, in 42 full factorial. The K2O levels positively influenced the length and mass of the plant and the number of seedlings per plant, while nitrogen levels influenced the leaf emergence and seedling mass. The N fertilization decreased the artificially induced flowering, while K increased flowering. The leaf mass 'D' showed the best correlation with fruit weight, being estimated a minimum mass of 44g to improve fruit 900g. Foliar N and K estimated at maximum doses tested were 13 g kg-1 and 32 g kg-1, respectively. The K did not influence the production variables. It was possible to register fruits with crown mass of 1086 g at the maximum dose of 365 kg ha-1 of N and yield of 42 t ha-1. The fertilization with N and without K increased the translucency linearly. With the increase of K, even at the highest dose of N, there was a decrease of the translucency of the fruits with a minimum point of 2.38 (on a scale of 1 to 5) physically, at a maximum of 400 kg ha-1 K2O. The N doses resulted linear decreases in SS and TA, while the pH and the ratio increased by increasing levels of N. The K2O levels increased linearly TA and SS, while the ratio decreased linearly. The fertilizer N promoted negative effects while potassium acted positively on the quality of 'BRS Imperial’ fruits